1990
DOI: 10.1073/pnas.87.12.4761
|View full text |Cite
|
Sign up to set email alerts
|

All-D amino acid-containing channel-forming antibiotic peptides.

Abstract: The D enantiomers of three naturally occurring antibiotics-cecropin A, magainin 2 amide, and melittin-were synthesized. In addition, the D enantiomers of two synthetic chimeric cecropin-melittin hybrid peptides were prepared. Each D isomer was shown by circular dichroism to be a mirror image of the corresponding L isomer in several solvent mixtures. In 20% hexafluoro-2-propanol the peptides contained 43-75% a-helix. The all-D peptides were resistant to enzymatic degradation. The peptides produced single-channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
492
2
4

Year Published

1992
1992
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 652 publications
(528 citation statements)
references
References 29 publications
23
492
2
4
Order By: Relevance
“…Enantiomeric forms of AMPs with D-amino acids only were used to investigate this membrane-binding mechanism (Wade et al, 1990;De Lucca et al, 2000;Bland et al, 2001). However, many studies illustrated that D-amino acid peptides have equal activities with their L-enantiomers (Wade et al, 1990;Hong et al, 1999;Wakabayashi et al, 1999;De Lucca et al, 2000;Bland et al, 2001;Hamamoto et al, 2002;Elmquist and Langel, 2003), suggesting that the antimicrobial mechanism of these peptides does not involve a stereoselective interaction with a chiral enzyme, lipid or protein receptor. However, some data indicate that the D-form AMPs have enhanced antimicrobial activity in vitro and in vivo due to higher stability against proteolysis degradation, which suggests higher clinical therapeutic potential (Vunnam et al, 1998;Chen et al, 2006;Jung et al, 2007).…”
Section: All D-form Of Aamps Increase Antimicrobial Activity and Stabmentioning
confidence: 99%
“…Enantiomeric forms of AMPs with D-amino acids only were used to investigate this membrane-binding mechanism (Wade et al, 1990;De Lucca et al, 2000;Bland et al, 2001). However, many studies illustrated that D-amino acid peptides have equal activities with their L-enantiomers (Wade et al, 1990;Hong et al, 1999;Wakabayashi et al, 1999;De Lucca et al, 2000;Bland et al, 2001;Hamamoto et al, 2002;Elmquist and Langel, 2003), suggesting that the antimicrobial mechanism of these peptides does not involve a stereoselective interaction with a chiral enzyme, lipid or protein receptor. However, some data indicate that the D-form AMPs have enhanced antimicrobial activity in vitro and in vivo due to higher stability against proteolysis degradation, which suggests higher clinical therapeutic potential (Vunnam et al, 1998;Chen et al, 2006;Jung et al, 2007).…”
Section: All D-form Of Aamps Increase Antimicrobial Activity and Stabmentioning
confidence: 99%
“…46 Results are in good agreement with those previously reported for these peptides under similar conditions (HFIP 12% (v/v) in buffer). 8,47 Spectra showed that CA(1-7)M(2-9) adopted a randomcoil structure in buffer, characterized by a minimum at ∼198 nm. In the presence of DMPC liposomes ( Figure 4A), there was a gradual red shift of the λ max of this negative band, which increased with lipid concentration.…”
Section: Calorimetrymentioning
confidence: 99%
“…Nevertheless, the precise mode of action of these antibacterial peptides is not yet fully understood. It has been suggested that the antibacterial activity appears to be due to the permeation of membranes via peptide-lipid interaction, rather than to receptor-mediated recognition [28,29]. To understand the structural requirements for this antibacterial activity, the enianto, retro, and retroenianto isomers of hybrid analogs of cecropin were synthesized [30].…”
Section: Antibacterial Mechanismsmentioning
confidence: 99%